Inter-cultivar variation in soil-to-plant transfer of radiocaesium and radiostrontium in Brassica oleracea. (May 2016) - Penrose, B.; Johnson née Payne, K.A.; Arkhipov, A.; Maksimenko, A.; Gaschak, S.; Meacham, M.C.; Crout, N.J.M.; White, P.J.; Beresford, N.A.; Broadley, M.R.
Abstract: Radiocaesium and radiostrontium enter the human food chain primarily via soil-plant transfer. However, uptake of these radionuclides can differ significantly within species (between cultivars). The aim of this study was to assess inter-cultivar variation in soil-to-plant transfer of radiocaesium and radiostrontium in a leafy crop species, Brassica oleracea. This study comprised four independent experiments: two pot experiments in a controlled environment artificially contaminated with radiocaesium, and two field experiments in an area contaminated with radiocaesium and radiostrontium in the Chernobyl Exclusion Zone. Radiocaesium concentration ratios varied 35-fold among 27 cultivars grown in pots in a controlled environment. These 27 cultivars were then grown with a further 44 and 43 other cultivars in the Chernobyl Exclusion Zone in 2003 and 2004, respectively. In the field-grown cultivars radiocaesium concentration ratios varied by up to 35-fold and radiostrontium concentration ratios varied by up to 23-fold. In three of these experiments (one pot experiment, two field experiments) one out of the 27 cultivars was found to have a consistently lower radiocaesium concentration ratio than the other cultivars. The two field experiments showed that, five out of the 66 cultivars common to both experiments had consistently lower radiocaesium concentration ratios, and two cultivars had consistently lower radiostrontium concentration ratios. One cultivar had consistently lower radiocaesium and radiostrontium concentration ratios. The identification of cultivars that have consistently lower radiocaesium and/or radiostrontium concentration ratios suggests that cultivar selection or substitution may be an effective remediation strategy in radiologically contaminated areas. Future research should focus on plant species that are known to be the largest contributors to human dose. Highlights: 35-fold variation in radiocaesium CRs was found among 70 Brassica oleracea cultivars. 23-fold variation in radiostrontium CRs was found among 70 B. oleracea cultivars. 5 cultivars were found to have consistently lower 137 Cs CRs. 3 cultivars were found to have consistently lower 90 Sr CRs. 1 cultivar was found to have consistently lower 137 Cs and 90 Sr CRs.